Solvent Responsive Self‐Folding of 3D Photosensitive Graphene Architectures. (21st April 2023) - Huang, Qi; Deng, Tao; Xu, Weinan; Yoon, ChangKyu; Qin, Zhao; Lin, Yida; Li, Tengfei; Yang, Yuqian; Shen, Michael; Thon, Susanna M.; Khurgin, Jacob B.; Gracias, David H.
Abstract : 3D Photoresponsive Microstructures In article number 2000195, Qi Huang, Tao Deng, Weinan Xu, ChangKyu Yoon, Zhao Qin, David Gracias, and co‐workers describe the design and highly parallel integration, assembly, and reversible reconfiguration of transparent 3D flexible graphene photodetector microstructures. The approach enables the creation of curved and folded devices that combine the flexibility of cross‐linked polymers with the functionality of 2D atomistic materials of importance to wearables, robotics, and biosensors.